2017
DOI: 10.1590/1678-98652017000500005
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of energy and macronutrient intake of food supplements for athletes

Abstract: A B S T R A C T ObjectiveTo assess how much food supplements contribute to the nutritional adequacy of energy and macronutrients in relation those recommended for athletes. MethodsThis was a cross sectional study was composed of 182 athletes from 19 sports (150 men and 32 women) with a mean age, weight, height and body mass index of 23.8±7.5 years, 73.7±15.6kg, 1.7±0.1m, 24.2±4.0kg/m², respectively. The 24 hours dietary recall was applied to assess intake and the Multiple Source Method to evaluate usual intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 19 publications
(23 reference statements)
1
3
0
6
Order By: Relevance
“…The majority of the athletes in the present study consumed less than the recommended amount of carbohydrates with no difference by sex. These results are corroborated by previous studies which have reported that many athletes, irrespective of sex did not meet the recommendations for carbohydrates [ 1 , 12 , 14 , 16 , 17 ]. Low carbohydrate intakes may lead to increased fatigue [ 47 ], negatively affect performance [ 48 ], and increase susceptibility to muscle damage [ 49 ] among athletes.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The majority of the athletes in the present study consumed less than the recommended amount of carbohydrates with no difference by sex. These results are corroborated by previous studies which have reported that many athletes, irrespective of sex did not meet the recommendations for carbohydrates [ 1 , 12 , 14 , 16 , 17 ]. Low carbohydrate intakes may lead to increased fatigue [ 47 ], negatively affect performance [ 48 ], and increase susceptibility to muscle damage [ 49 ] among athletes.…”
Section: Discussionsupporting
confidence: 90%
“…Energy needs were not met by most athletes. This was unsurprising given that several previous studies have reported that many athletes do not meet their energy needs [ 10 , 11 , 12 , 13 ]. The majority of the athletes in the present study consumed less than the recommended amount of carbohydrates with no difference by sex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A redução da fadiga e de lesões e o aumento da ingestão calórica são alguns dos diversos benefícios das intervenções nutricionais, documentados nos estudos (PANZA et al, 2007;ROY, 2008) DO ESPORTE, 2009). Contudo, uma ingestão dietética inadequada ainda é muito observada em atletas (GOMES et al, 2009;RODRIGUES et al, 2017).…”
Section: Introductionunclassified